Inside Back Cover: Discovery of Hepatitis C Virus NS3 Helicase Inhibitors by a Multiplexed, High‐Throughput Helicase Activity Assay Based on Graphene Oxide (Angew. Chem. Int. Ed. 8/2013). Issue 8 (28th January 2013) - Jang, Hongje; Ryoo, Soo‐Ryoon; Kim, Young‐Kwan; Yoon, Soojin; Kim, Henna; Han, Sang Woo; Choi, Byong‐Seok; Kim, Dong‐Eun; Min, Dal‐Hee
<x xml:space="preserve">Abstract</x> DNA helicases are important targets for anti‐viral drug development. In their Communication on page 2340 ff., D.‐H. Min et al. use graphene oxide for high‐throughput chemical screening to discover new inhibitors of two different helicases derived from hepatitis C virus and severe acute respiratory syndrome (SARS) coronavirus in a multiplexed assay. The developed assay can also be used to validate hits from the helicase inhibitor screen.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>